Context-sensitive evaluation: Determining the context surrounding the implementation of a government policy. (December 2015) - Alderman, Lyn
This article explains the essence of the context-sensitive parameters and dimensions in play at the time of an intervention, through the application of Rog's (2012) model of contextual parameters. Rog's model offers evaluators a structured approach to examine an intervention. The initial study provided a systematic way to clarify the scope, variables, timing, and appropriate evaluation methodology to evaluate the implementation of a government policy. Given that the government implementation of an educational intervention under study did not follow the experimental research approach, nor the double cycle of action research approach, the application of Rog's model provided an in-depth understanding of the context-sensitive environment; it is from this clear purpose that the broader evaluation was conducted. Overall, when governments or institutions implement policy to invoke educational change (and this intervention is not guided by an appropriate evaluation approach), then program evaluation is achievable post-implementation. In this situation, Rog's (2012) model of contextual parameters is a useful way to achieve clarity of purpose to guide the program evaluation.